Struggle of Love Elizabeth and Darcy As Seen in Jane Austen`S Pride and Prejudice - Astuti, Amelia Yuli; Aloysius, Aloysius (Jurnal Ilmiah Pendidikan Scholastic, 2025)
This thesis focuses on the love struggle between Elizabeth and Darcy, the conflict between them is prejudice and pride. Prejudice is found in Elizabeth and pride is found in Darcy, this thesis uses Steinberg's triangular theory of love with three main components such as intimacy, passion, and commitment. The method used in this research is descriptive qualitative. To obtain by searching and collecting several books related to analyzing the struggle of love, sacrifice, and external conflict in a literary work. By quoting sentences or words that show the characteristics of love struggles and forms of sacrifice, as well as external conflicts and then transcribing them. This thesis focuses on Elizabeth and Darcy love struggle, the conflict between them is prejudice and pride. Prejudice is found in Elizabeth and pride is found in Darcy. The result of the research is that Elizabeth and Darcy's love struggle is caused by the conflict between them, and the conflict comes from their own personalities, how to deal with prejudice and arrogance, especially the difference in social status class, Darcy comes from a rich family and Elizabeth comes from a low social status class family. This became a tense conflict between Elizabeth and Darcy in their love journey. After the change of attitude between them, they had to face reality, because in the change of attitude, they realized that what they had done such as prejudice by Elizabeth and arrogance from Darci caused them to understand each other, they admitted their mistakes, apologized, accepted each other's opinions and forgave each other. This pushes them to go through conflicts that are very difficult to be united in their journey of love.